Functional Outcome of Unilateral Peroneus Longus Autograft in Arthroscopic Anterior Cruciate Ligament Reconstruction - Munir, Shahid; Wajahat Ali Nadeem; Muhammad Nadeem; Raza, Ali; Malik, Ahmed Tariq; Siddique, Zeeshan (Pakistan Armed Forces Medical Journal, 2023)
Objective: To evaluate the functional outcome of unilateral peroneus longus autograft in arthroscopic anterior cruciate ligament reconstructionStudy Design: Cross-sectional study.Place and Duration of Study: Orthopedic Department, Combined Military Hospital, Lahore Pakistan, from Jul 2020 to Jun2021.Methodology: We included all the patients who underwent ipsilateral peroneus longus autograft for anterior cruciate ligament reconstruction. Fixation was achieved with a bio-absorbable screw on the tibial side and an endobutton on the femoral side. Lateral or medial menisectomy was performed according to the requirement. Post-op X-rays were done to assess the position of the endobutton and tibial tunnel. Eight millimetres tunnels were drilled, and the tendon was tailored accordingly. Results were assessed for pain, infection, range of motion and instability after three months of surgical procedure.Results: A total of 52 patients were included in the final analysis. The mean age of the study participants was 33.36±6.353 years. At the end of three months, pain 6(11.5%) and restricted range of motion 6(11.5%) were the common untoward outcomes reported by the patients. High body mass index and lack of engagement in physiotherapy had a statistically significant relationship with the presence of untoward outcomes in our study (p-value